Clinical characterization, physical frailty, and depression in elderly patients with psoriasis from a reference center in Brazil: a cross-sectional study - Brandão, Giovana Viotto Cagnon [UNESP] (2024)
Background: There are few studies dedicated to the characterization of the geriatric population with psoriasis, which has particularities in terms of clinical manifestations and therapeutic limitations. As psoriasis is a chronic disease, presenting a higher prevalence with age, the increase in life expectancy in Brazil demands knowledge about the behavior of the disease among the elderly. Objectives: To characterize elderly people with psoriasis from a tertiary service, from the clinical-epidemiological point of view, presence of comorbidities, physical frailty, and affective impact, and to compare these aspects with adults with psoriasis and elderly people without the disease. Methods: Cross-sectional study of 64 elderly patients with psoriasis, 64 adults with psoriasis, and 64 elderly patients without the disease. Clinical-demographic aspects, the Beck depression scale, and Skindex-16 were evaluated. Indicators of physical frailty were evaluated in elderly patients: handgrip, sit-to-stand test, fatigue, and weight loss >5%. Results: In the elderly, the mean age (SD) of psoriasis onset was 44 (10) years, men represented 47% of the sample, the prevalence of arthritis was 22%, and ungual involvement occurred in 72%. Topical corticosteroids were used more often among elderly people with psoriasis (100%) than among adults with the disease (86%), with no difference among other systemic treatments. Diabetes mellitus occurred in 30% of the elderly. Hypertension (59%), dyslipidemia (52%), depression (34%), and fatigue (59%) were more prevalent among the elderly with psoriasis than among the healthy controls. Study limitations: The study was carried out in a public reference service for patients with psoriasis, all of which were undergoing treatment. Conclusions: Elderly people with psoriasis from a tertiary service showed greater affective impairment, metabolic comorbidities, and physical frailty than elderly controls.